Evolution of coke properties while descending through a blast furnace - Hilding, Tobias (Luleå tekniska universitet, 2005)
Due to increasing price and economic pressures, there is a need to minimise coke consumption. The lesser amount of coke used has indirectly set higher standards for coke quality and led to a wish for even more knowledge about its function in the blast furnace. Over the last 20 years, coke quality has been strongly dictated by the so- called CSR value because it was believed that a higher CSR leads to improvement in productivity and more stable operation. Due to lack of suitable coals, often cokes are made from coals with relatively inferior coals leading to coke with lower values of the so-called CRI indicia. Because of this, there was an indirect focus on cokes with lower CRI values. Therefore, this thesis will address some of the important issues of coke strength and focus on changes occurring with coke when it passes through a blast furnace. The main aim of this study is to understand the degradation mechanisms and reactivity changes of coke in order to investigate the factors that affect coke quality. Cokes excavated from LKAB's Experimental Blast Furnace (EBF) are used as a basis for the research. Two campaigns with similar coke (low CRI/high CSR) but different blast furnace injection material have been studied. The coke is supplied from SSAB Tunnplåt Luleå AB. Physical and chemical properties of cokes samples from the EBF were measured. Evolution of coke properties particularly carbon structure and alkali uptake were related to CO2 reactivity as well as coke behaviour (e.g. CSR/abrasion). In addition to this, a trial with very high CRI coke was studied. On the basis of this study, following conclusions were made. The order of carbon structure and concentration of alkali species were increased and these were the most notable changes in the coke properties as it passed through shaft to the cohesive zone of the EBF. The degree of graphitisation was increased while amorphous carbon content was decreased in the hotter zones of the EBF. A linear correlation between the height of the carbon crystallite (Lc) ...